Apoios e interdições ao protagonismo de jovens em medidas socioeducativas em meio aberto - Silva, Henrique Manoel Carvalho (2023)
This thesis, entitled "Supports and Restrictions to Youth Protagonism in Open SocioEducational Measures," aims to understand the compatibility of Youth Protagonism with Open Socio-Educational Measures (MSE/MA), such as Supervised Freedom (SF) and/or Community Service (CS). The study begins with a historical contextualization of the categories of adolescence and youth in the Brazilian context, highlighting contemporary challenges such as education, employment, families, and violence. It acknowledges the diversity of youth. The second chapter explores the understandings and discourses on Youth Protagonism. It also analyzes the relationship with the Unified Social Assistance System (SUAS), the National SocioEducational Assistance System (SINASE), and specific legislation for the social protection of adolescents and youth. The research examines the legal context surrounding the development of Individualized Service Plans (ISP) and their impact on the protagonism of adolescents and young people. The third phase reports on the field research, highlighting the interaction with the participants and analyzing their experiences in light of the identified categories. The final considerations synthesize the theoretical framework, research field perceptions, and observations throughout the investigative process. The study uses bibliographic research, focus groups, and oral history to capture the perspectives of workers in MSE/MA Services and the adolescents and young people involved